Epidermolysis bullosa with pyloric atresia associated with compound heterozygous ITGB4 pathogenic variants: Minimal skin involvement but severe mucocutaneous disease. Issue 4 (21st June 2021) - Wee, Lynette Wei Yi; Tan, Ene Choo; Bishnoi, Priya; Ng, Yi Zhen; Lunny, Declan Patrick; Lim, Hwee‐Woon; Lee, Siew‐Peng; Ong, Christina; Yap, Te Lu; Mok, Yee Hui; Low, Mei Yi; Chu‐Tian Chow, Cristelle; et al.
Abstract: We report a case of junctional epidermolysis bullosa with pyloric atresia (JEB‐PA) with minimal skin involvement but severe protein‐losing enteropathy and airway involvement. Genetic analysis revealed heterozygous mutations in the ITGB4 gene encoding integrin β4 protein. Parental testing confirmed inheritance of frameshift variant (c.794dupC) as maternal and splice site variant (c.1608C>T/p.Cys536Cys) as paternal. Immunofluorescence mapping of her skin revealed a subepidermal blister with decreased and frayed integrin β4 at both the floor and the roof of the blister, while the intestinal mucosa showed complete absence of integrin β4. We review the literature and discuss the differential expression of integrins in the skin and gastrointestinal tract, as well as the role of chronic inflammation in the pathogenesis of EB.